P2X7 receptor antagonism ameliorates renal dysfunction in a rat model of sepsis. Issue 5 (27th February 2018) - Arulkumaran, Nishkantha; Sixma, Marije L.; Pollen, Sean; Ceravola, Elias; Jentho, Elisa; Prendecki, Maria; Bass, Paul S.; Tam, Frederick. W. K.; Unwin, Robert J.; Singer, Mervyn
Abstract: Sepsis is a major clinical problem associated with significant organ dysfunction and high mortality. The ATP‐sensitive P2X7 receptor activates the NLRP3 inflammasome and is a key component of the innate immune system. We used a fluid‐resuscitated rat model of fecal peritonitis and acute kidney injury (AKI) to investigate the contribution of this purinergic receptor to renal dysfunction in sepsis. Six and 24 h time‐points were chosen to represent early and established sepsis, respectively. A selective P2X7 receptor antagonist (A‐438079) dissolved in dimethyl sulfoxide (DMSO) was infused 2 h following induction of sepsis. Compared with sham‐operated animals, septic animals had significant increases in heart rate (−1(−4 to 8)% vs. 21(12–26)%; P = 0.003), fever (37.4(37.2–37.6)°C vs. 38.6(38.2–39.0)°C; P = 0.0009), and falls in serum albumin (29(27–30)g/L vs. 26(24–28); P = 0.0242). Serum IL‐1 β (0(0–10)(pg/mL) vs. 1671(1445–33778)(pg/mL); P < 0.001) and renal IL‐1 β (86(50–102)pg/mg protein vs. 200 (147–248)pg/mg protein; P = 0.0031) were significantly elevated in septic compared with sham‐operated animals at 6 h. Serum creatinine was elevated in septic animals compared with sham‐operated animals at 24 h (23(22–25) μ mol/L vs. 28 (25–30) μ mol/L; P = 0.0321). Renal IL‐1 β levels were significantly lower in A‐438079‐treated animals compared with untreated animals at 6 h (70(55–128)pg/mg protein vs. 200(147–248)pg/mg protein; P = 0.021). At 24 h, compared with untreated animals, A‐438079‐treated animals had more rapid resolution of tachycardia (22(13–36)% vs. −1(−6 to 7)%; P = 0.019) and fever (39.0(38.6–39.1)°C vs. 38.2(37.6–38.7)°C; P < 0.024), higher serum albumin (23(21–25)g/L vs. (27(25–28)g/L); P = 0.006), lower arterial lactate (3.2(2.5–4.3)mmol/L vs. 1.4(0.9–1.8)mmol/L; P = 0.037), and lower serum creatinine concentrations (28(25–30) μ mol/L vs. 22(17–27) μ mol/L; P = 0.019). P2X7 A treatment ameliorates the systemic inflammatory response and renal dysfunction in this clinically relevant model of sepsis‐related AKI. Abstract : Sepsis‐induced acute kidney injury (AKI) is a major clinical problem associated with significant organ dysfunction and high mortality. A rat model of sepsis demonstrated upregulation of renal tubular cell P2X7 receptor in sepsis. P2X7 antagonist treatment ameliorates the systemic inflammatory response and renal dysfunction in this clinically relevant model of sepsis‐related AKI.